Sociology of corruption: patterns of illegal association in Hungary - Jancsics, David (Cornell University Press, 2024)
"This book offers a novel sociological theory of corruption and uses it as a framework to make sense of rich ethnographic data, which includes more than one hundred in-depth interviews collected in Hungary over ten years of fieldwork."--